Categorization of the Undertakings as a Postulate for Financial Reporting Tailored to the Needs of Users - Boyanov, Borislav (Research Papers, 2021)
The topicality of the theme of the categorization of undertakings for accounting purposes arises from the ever-changing capabilities and needs of users of financial statements on a national, regional and global scale. The accounting categorization of undertakings shall be considered as a starting point for the establishment and operation of accounting systems which correspond to the dimensions, objectives and needs of internal and external users of information from the financial statements. Therefore, the process of categorizing undertakings should be one of the significant conditions by which user feedback on accounts to the accounting systems of undertakings is met.
Keywords: Conceptual clustering; Categorization; Undertakings; Accounting; Financial reports